Silagens de sorgo aditivadas com torta de algodão e inoculantes microbianos - Justino, Evandra da Silva (2021)
The objective was to evaluate the fermentative profile, microbial populations, aerobic stability, bromological characteristics and losses of forage sorghum silages added with cotton cake and microbial inoculants. Two experiments were carried out using forage sorghum (Sorghum bicolor (L.) Moench.) Cultivar BRS Ponta Negra. In the first experiment, levels of cotton cake were evaluated in association with sorghum for silage, and the opening was performed at 55 days after ensiling. A completely randomized design was used, with 5 treatments and 4 repetitions. The treatments were arranged as follows: T1 = only forage sorghum; T2 = forage sorghum + 5% cotton cake; T3 = forage sorghum + 10% cotton cake; T4 = forage sorghum + 20% cotton cake; T5 = forage sorghum + 40% cotton cake. The use of cotton cake as a nutritional additive reduced fermentative losses, increased the recovery of dry matter, improved aerobic stability and increased the nutritional value of the added silages. At the levels assessed in the present study, it is recommended to use 20% cotton cake inclusion. In the second experiment, the cotton cake was evaluated in association with the microbial inoculants, with opening of the silos 45 and 90 days after ensiling. A completely randomized design was used in a 2 x 4 factorial scheme, with 4 replications, with the following treatments Sorghum (Control) being analyzed; Sorghum + 20% cotton cake (Control); Sorghum + L. plantarum; Sorghum + 20% cotton cake + L. plantarum; Sorghum + W. cibaria; Sorghum + 20% cotton cake + W. cibaria; Sorghum + Combo; Sorghum + 20% cotton cake + Combo. The use of cotton cake improved fermentative characteristics, decreased effluent losses, increased nutritional value, increased dry matter recovery and, due to yeast inhibition, improved aerobic stability. Weissella Cibaria in association with cotton cake significantly reduced the development of yeasts in sorghum silage with opening at 90 days. Weissella Cibaria and Lactobacillus plantarum in combination (combo) controlled the fungi in the sorghum silage. Lactobacillus plantarum was able to acidify the medium even under conditions of greater buffering capacity.